The Coal Humic Product EldORost Shows Fertilizing and Growth Stimulating Properties on Diverse Agricultural Crops - Oral T. Zhilkibayev; Temirzhan E. Aitbayev; Anastasiya M. Zhirkova; Irina V. Perminova; Alexander I. Popov; Sabina A. Shoinbekova; Mukhtar S. Kudaibergenov; Kairzhan M. Shalmaganbetov (Agronomy, 2022)
The use of environmentally safe products of natural origin is a global trend today. A particular point of interest is the use of humic fertilizers. This is due to the growing awareness of the positive impact of humic substances on plant growth and development as well as on the quality of agricultural products and soil fertility. Humates are physiologically active substances. As a result, they regulate and intensify metabolic processes in plants and soil, and contribute to the bioavailability of nutrients to plants. EldORost is a new-generation humic product that contains humic substances with a high humification degree. In addition to humates, this product contains a complex of amino acids, macro-, and microelements in a bioavailable form for plants. The product is eco-friendly and completely soluble in water, which is a substantial advantage for drip irrigation systems. It can be used for all types of agricultural crops on a wide diversity of soils and climatic zones. It displays the properties of plant hormones while its optimum concentration is as low as 0.0001% (wt). The efficiency of this novel humic product was tested in laboratory and field tests conducted on potatoes and vegetable crops (tomatoes, cucumbers, cabbage, carrots, onions, beets). The obtained results showed high efficiency displayed in the significantly improved sowing quality of vegetable seeds, nominally increased the germination degree and seed germination energy, intensively stimulated the side root development in plants, accelerated the growth of biomass, increased the fruiting period, and reduced maturation on the yield of potatoes and vegetable crops. The obtained data allowed us to characterize this novel humic product from the perspective of an eco-friendly fertilizer and growth promoter.